Annual, Smithsonian fitness of Man's environment (Washington, 1966)
The papers constrained in this volume represent a group of carefully selected experts who over the past six months have prepared statement concerning the principles which should guide the development of the physical environment of man.
The first volume in the Smithsonian Annual Series, Knowledge among men , was published by Simon and Schuster in 1966
Keywords: Environment